Illicium floridanum Florida Anise Tree, Florida Anise - Edward Gilman (EDIS)
This document provides a detailed overview of the Florida anise tree (Illicium floridanum), a native shrub of Florida. It describes the plant’s physical characteristics, including its olive green leaves, reddish-purple flowers, and star-shaped seed pods. The document outlines the plant’s growth habits, preferred growing conditions, and uses in landscaping. It also highlights the plant’s moderate drought tolerance, pest resistance, and ease of maintenance. Additionally, it mentions the propagation methods and the availability of a white-flowered cultivar named ‘Album’. Original publication date October 1999.